Transcriptional data analysis reveals the association between infantile hemangiomas and venous malformations - Huang, Biao; Zhang, Ping; Zhong, Yuan-Yuan; Wang, Kuan; Chen, Xiao-Ming; Yu, Dao-Jiang (Frontiers in Genetics, 2022)
Background Infantile hemangiomas (IH) and venous malformations (VM) are the most common types of vascular abnormalities that seriously affect the health of children. Although there is evidence that these two diseases share some common genetic changes, the underlying mechanisms need to be further studied. Methods The microarray datasets of IH (GSE127487) and VM (GSE7190) were downloaded from GEO database. Extensive bioinformatics methods were used to investigate the common differentially expressed genes (DEGs) of IH and VM, and to estimate their Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Trough the constructing of protein-protein interaction (PPI) network, gene models and hub genes were obtained by using Cytoscape and STRING. Finally, we analyzed the co-expression and the TF-mRNA-microRNA regulatory network of hub genes. Results A total of 144 common DEGs were identified between IH and VM. Functional analysis indicated their important role in cell growth, regulation of vasculature development and regulation of angiogenesis. Five hub genes (CTNNB1, IL6, CD34, IGF2, MAPK11) and two microRNA (has-miR-141-3p, has-miR-150-5p) were significantly differentially expressed between IH and normal control (P<0.05). Conclusion In conclusion, our study investigated the common DEGs and molecular mechanism in IH and VM. Identified hub genes and signaling pathways can regulate both diseases simultaneously. This study provides insight into the crosstalk of IH and VM and obtains several biomarkers relevant to the diagnosis and pathophysiology of vascular abnormalities.